Network structures and heterogeneity in policy preferences at the FOMC - Arnab Bhattacharjee; Sean Holly; Mustapha Wasseja (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
Transcripts from the US Federal Open Markets Committee provide, albeit with a lag, valuable information on the monetary policymaking process at the Federal Reserve Bank. We use the data compiled by Chappell et al. (2005b) on preferred interest rates (not votes) of individual FOMC members. Together with information on which monetary policy decisions are based, we use these preferred rates to understand decision making in the FOMC, focussing both on cross-member heterogeneity and interaction among the members of the committee. Our contribution is to provide a method of unearthing otherwise unobservable interactions between the members of the FOMC. We find substantial heterogeneity in the policy reaction function across members. Further, we identify significant interactions between individuals on the committee. The nature of these interdependencies tell us something about information sharing and strategic interactions within the FOMC and provide interesting comparisons with the Bank of England's Monetary Policy Committee.
Keywords: E42; E43; E50; E58; C31; C34; 330; Monetary policy; Interest rates; FOMC decision making; Spatial Weights Matrix; Spatial Lag Model